Continuity and Change in U.S. Foreign Policy toward Southern Africa: Assessing the Clinton Administration (Nordic Journal of African Studies, 2001)
This paper analyses the foreign policy of the Clinton (1993-2001) administration toward Southern Africa building on field interviews conducted with U.S. diplomats in Botswana, South Africa and Zimbabwe. The paper is divided into five sections, each of which highlights a specific trend in U.S. foreign policy toward Southern Africa: the centrality of trade in U.S. foreign policy; the 'regionalization' of foreign policy initiatives; bureaucratic dominance of the U.S. policymaking process; reassessments of direct U.S. involvement in African conflicts; and an uneven approach to democracy promotion. These trends are principally highlighted by drawing on the case studies of Botswana, South Africa, and Zimbabwe, although reference is also made to Angola, Lesotho, Malawi, Mozambique, Namibia, and Zambia. A final section offers general conclusions, including what one can expect from the newly inaugurated administration of President George W. Bush (2001-present).